A preliminary study of perception on diction among vocal students at faculty of music UiTM / Nurul Fazlina Ariff Fadillah - Ariff Fadillah, Nurul Fazlina (Faculty of Music, 2013)
This study was carried out in 2012 in the Faculty of Music, Universiti Teknologi MARA, Shah Alam. The scope of study focuses on Diploma and Degree music students, whose majoring voice as their principal studies during the period of their programs. This study was initiated basing on feedback from the respondents with regarding the importance of diction. The main objectives of this study are; 1) to explore voice major's perception on the importance and benefits of learning diction; and 2) To investigate the causes that make students lack of diction knowledge in their learning process. Analysis was done using the manual calculation. This study concluded that most of the respondents realize that diction is important in their performance; however the lack of knowledge causes the problem. With encouragement by the lecturers and the faculty, the students are motivated to learn diction and aware about the importance of diction.